EFL teacher`s teaching strategies and problem during COVID 19 outbreak in Indonesian junior high school - Meilisa Khairiani; Alfian Alfian; Dharma Putra (Journal on Education, 2022)
The aims of this study are to find the teaching strategies applied by EFL teacher and the problem at Junior a High School in Indonesia. The design of the research is descriptive qualitative. The researcher use observation, interview and documentation to collect the data. While, to analyze the data researcher used qualitative narrative appoarch. The steps were : create and organize files for data, read through text, make(margin notes, form initial codes), describe the story or objective set of experiences and place it in a chronology, identify stories and contextual materials, interpret the larger meaning of the story, and present narration (focusing on processes theories, and unique and general features of the life). In addition, the result of this research showed ; 1) the EFL teacher using syncronous to online teaching; 2) the problem in online taching are lack of quota package, lack of internet access, lack of motivation, and lack of facilities.